2014
DOI: 10.4103/2008-322x.150800
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of autologous ex vivo expanded human conjunctival epithelial cells for treatment of pterygia: A prospective open-label single arm multicentric clinical trial

Abstract: Purpose:To establish the efficacy and safety of ex vivo cultured autologous human conjunctival epithelial cell (hCjEC) transplantation for treatment of pterygia.Methods:Twenty-five patients with pterygia were recruited at different centers across the country. Autologous hCjEC grafts were prepared from conjunctival biopsy specimens excised from the healthy eye and cultured ex vivo on human amniotic membrane mounted on inserts using a unique mounting device. The hCjEC grafts were then transported in an in-house … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…This study prepares the way for such future work by providing analyses that represent a thorough characterization of stored sheets at each temperature. A future clinical trial might follow a similar design to that recently conducted by Vasania et al 57 , where cultured human conjunctival epithelial cells were transported to four regional centers from a centralized culture facility in India. Transplants were successfully used to treat patients with pterygium following transport 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study prepares the way for such future work by providing analyses that represent a thorough characterization of stored sheets at each temperature. A future clinical trial might follow a similar design to that recently conducted by Vasania et al 57 , where cultured human conjunctival epithelial cells were transported to four regional centers from a centralized culture facility in India. Transplants were successfully used to treat patients with pterygium following transport 57 .…”
Section: Discussionmentioning
confidence: 99%
“…A future clinical trial might follow a similar design to that recently conducted by Vasania et al 57 , where cultured human conjunctival epithelial cells were transported to four regional centers from a centralized culture facility in India. Transplants were successfully used to treat patients with pterygium following transport 57 . A trial such as this might employ the optimal conditions outlined in the present study and transport CES for treatment of patients with chronic skin ulcers, which is an operation that can be scheduled in advance.…”
Section: Discussionmentioning
confidence: 99%
“…Vasania et al . found a viability of 78–90% after transport of up to 48 hours for conjunctival tissue 16 . The present study suggests that vigorous shaking does not appear to cause cell death.…”
Section: Discussionmentioning
confidence: 96%
“…In 2014, Vasania et al . tested an in-house designed transportation container for cultured conjunctival epithelial cell sheets on human amniotic membrane (HAM), with viable, intact epithelial sheets upon arrival and good post-operative outcome for pterygium surgery 16 . Oie et al .…”
Section: Introductionmentioning
confidence: 99%
“…Oie et al demonstrated that cultured oral mucosal cell sheets retained viability and phenotype following 12 hours transportation in Japan [ 4 ]. Moreover, cultured conjunctival epithelial cells were successfully used for treatment of pterygium in 23 patients following distribution to four eye clinics in India [ 5 ]. Advantages of a standardized short-term storage and transport method for cultured HLEC include provision of a window for sterility and quality assessment, improved surgery logistics, and wider access to treatment.…”
Section: Introductionmentioning
confidence: 99%